تأثير تمرينات خاصة على وفق بعض المؤشرات الكينماتيكية في تطوير بعض القدرات البدنية ومستوى الانجاز بالقفز العالـي - حسين, احلام صادق; علي, لقاء عبدالله (Sulaimani Journal for Humanities, 2018)
This study comes in the use of exercises according to some Elkinmetekih variables in the effectiveness of the high jump in some physical abilities and level of achievement among the players. The research aims to identify: 1-preparation curriculum of exercises according to some Elkinmetekih variables in some of the physical abilities and the level of achievement of the effectiveness of the high jump. 2-identify the impact of exercise on Elkinmetekih according to some variables in some of the physical abilities and the level of achievement of the effectiveness of the high jump. Research hypotheses: - In the light of the objectives of the research puts the researcher the following assumptions: - 1 There are significant differences between tribal and dimensional tests in some physical abilities differences. 2. There are significant differences between the results of the tests and tribal dimensionality and the level of achievement of the effectiveness of the high jump. The use of the experimental method has been selected sample of players Specialized School Games track and field in Baghdad to the effectiveness of the high jump and the number (5) players from the youth category. And it yielded results contributed exercises according to some Elkinmetekih variables included in the training curriculum in the development of physical capabilities and the level of achievement the players to sample, has been recommending to rely on exercise for when developing the physical abilities and the level of achievement of the effectiveness of the high jump.